2007
DOI: 10.1016/j.clinbiomech.2007.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the material properties of the subsynovial connective tissue in carpal tunnel syndrome

Abstract: Background: The purpose of this study was to determine the material properties of the normal carpal tunnel subsynovial connective tissue in response to shear stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
53
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 17 publications
5
53
0
1
Order By: Relevance
“…Although the clinical aspect of this disease has been well studied, its cause remains unknown 8,9 . Changes in mechanical properties and fibrosis of the subsynovial connective tissue within the carpal tunnel are the major pathological findings in patients with carpal tunnel syndrome 10,11 . Although these changes may hinder mediannerve gliding 12 and lead to elevated local strains and pressures, so far there is no way to diagnose the cause of this condition.…”
mentioning
confidence: 99%
“…Although the clinical aspect of this disease has been well studied, its cause remains unknown 8,9 . Changes in mechanical properties and fibrosis of the subsynovial connective tissue within the carpal tunnel are the major pathological findings in patients with carpal tunnel syndrome 10,11 . Although these changes may hinder mediannerve gliding 12 and lead to elevated local strains and pressures, so far there is no way to diagnose the cause of this condition.…”
mentioning
confidence: 99%
“…[6] This phenomenon results in a vicious cycle of increased shearing force throughout SSCT because fibrosis increases both the stiffness of the tissue and shearing modulus that inevitably result in shearing force to be much more effective. [7,8] Fibroblasts are effective mechano-responsive cells. [9] It is shown that fibroblasts respond to tension, compression and shearing forces with expression of different genes, and they can even change their phenotype to more fibrotic cells such as myofibroblasts.…”
mentioning
confidence: 99%
“…Some studies have investigated the fibrosis of the subsynovial connective tissue (SSCT) encasing the flexor tendons as a contributing factor in the etiology of primary CTS. [3][4][5][6] In 2004, Ettema et al demonstrated marked proliferation and fibrosis of the SSCT in patients with established primary CTS. It was suggested that this resulted in increased carpal tunnel pressures that could give rise to CTS.…”
Section: Introductionmentioning
confidence: 98%